EFEKTIFITAS PENYULUHAN MENGGUNAKAN MEDIA WHATS-APPS TERHADAP TINGKAT PENGETAHUAN KESEHATAN GIGI IBU HAMIL DI KABUPATEN BANGLI TAHUN 2021 - Sagung Agung Putri; Cok Ari; Dewi Kumala Ratih; Ni Wayan Arini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2022)
Pregnant women are a group prone to dental and oral diseases, the increase in the hormone progesterone can be ten times higher than usual, which causes inflammation of the gums and lowered immunity. The purpose of this study was to determine the effectiveness of counseling using what-Apps media on the level of dental health knowledge of pregnant women in Bangli. The design of this study was a pre-experimental study with a one-group pre- and post-test design. This research was conducted in Bangli, the population in this study were pregnant women in the IPE KKN area in Bangli, the number of samples in this study was taken as many as 30 people who were taken by purposive sampling. The criteria for inclusion of the sample in this study were at the time of the study the mother was pregnant, had a smart phone, had a WhatsApp application, and a google form. The instrument of this research is a questionnaire about dental health in the form of multiple choice with 4 options. Data collection is done online using google form. Data is presented in narrative, table, and graphic manner, analyzed quantitatively by univariate and bivariate. The effectiveness of counseling using WhatsApps media on the level of dental health knowledge of pregnant women in Bangli was analyzed using a paired t test. The results of the analysis showed that the average level of knowledge before counseling was 67.10, the average level of knowledge after counseling was 89.87, with p value = 0.000. The conclusion of counseling using what-Apps media is effective on the level of dental health knowledge of pregnant women in Bangli